ApoB-48 and apoB-100 differentially influence the expression of type-III hyperlipoproteinemia in APOE*2 mice - Myron E. Hinsdale (Journal of Lipid Research, 2002)
Apolipoprotein E (apoE) is essential for the clearance of plasma chylomicron and VLDL remnants. The human APOE locus is polymorphic and 5–10% of APOE*2 homozygotes exhibit type-III hyperlipoproteinemia (THL), while the remaining homozygotes have less than normal plasma cholesterol. In contrast, mice expressing APOE*2 in place of the mouse Apoe (Apoe2/2 mice) are markedly hyperlipoproteinemic, suggesting a species difference in lipid metabolism (e.g., editing of apolipoprotein B) enhances THL development. Since apoB-100 has an LDLR binding site absent in apoB-48, we hypothesized that the Apoe2/2 THL phenotype would improve if all Apoe2/2 VLDL contained apoB-100. To test this, we crossed Apoe2/2 mice with mice lacking the editing enzyme for apoB (Apobec−/−). Consistent with an increase in remnant clearance, Apoe2/2 · Apobec−/− mice have a significant reduction in IDL/LDL cholesterol (IDL/LDL-C) compared with Apoe2/2 mice. However, Apoe2/2 ·Apobec−/− mice have twice as much VLDL triglyceride as Apoe2/2 mice. In vitro tests show the apoB-100-containing VLDL are poorer substrates for lipoprotein lipase than apoB-48-containing VLDL.Thus, despite a lowering in IDL/LDL-C, substituting apoB-48 lipoproteins with apoB-100 lipoproteins did not improve the THL phenotype in the Apoe2/2 ·Apobec−/− mice, because apoB-48 and apoB-100 differentially influence the catabolism of lipoproteins.